DESAIN LKS BERBASIS VIRTUAL LABORATORY MELALUI ICT PADA MATERI FLUIDA DINAMIS, SUHU DAN KALOR, SERTA TEORI KINETIK GAS KELAS XI - novelia prima; masril masril; hidayati hidayati; yenni darvina (PILLAR OF PHYSICS EDUCATION, 2018)
The problem that underlies this research is the less optimal of practice implementation because of the limitations of tools and time implementation. Solution to help the implementation of the real practicum is to implement virtual laboratory. There have been several virtual laboratory related physics materials available on the internet such as phet. It's just not been able to be used by students because there is no worksheet that support the application for use on practicum activities. Therefor, the researcher develops student’s worksheet for virtual laboratory through ICT to support student practicum activity on dynamic fluid material, temperature and heat, and gas kinetic theory for XI grade. The research includes research and development (R & D) with 4D model. This study consists of 4 steps that are limited to the third step, namely define, design, and develop. The object of the research is student’s worksheet for virtual laboratory through ICT on dynamic fluid material, temperature and heat, and gas kinetic theory which tested to grade XI student of SMA Negeri 1 Padang. Based on data analysis that has been done can be presented two research results. First, student’s worksheet based on virtual laboratory is in valid category with validation value 77,14. Second, the practicality category of student’s worksheet based on virtual laboratory is very practical with practical value according to teacher 88,46 and practicality value according to student 86,40.